Separation, Purification, Structural Characterization and in Vitro Antioxidant Activity of Low Molecular Mass Fucoidans - YU Fan, GUO Yingying, LI Na, DAI Xinyue, ZHU Wenjia, YAO Lin, JIANG Yanhua, WANG Lianzhu (Shipin Kexue)
In this study, two low molecular mass fucoidans (LMWFs), F-1 and F-2, derived from Undaria pinnatifida fucoidan, were prepared and purified by free radical oxidation degradation and strong anion exchange chromatography. The chemical composition and structure characteristics of LMWFs were analyzed using molecular exclusion chromatography (MEC), high performance liquid chromatography (HPLC), infrared spectroscopy (IRS) and nuclear magnetic resonance spectroscopy (NMRS), and the structure-antioxidant activity relationship was explored. The results showed that F-1 and F-2 were primarily composed of fucose and galactose, with molecular mass of 2 790 and 23 510 Da, respectively. Their sulfate contents were (27.05 ± 0.95)% and (34.73 ± 0.08)%, and their uronic acid contents were (15.39 ± 0.33)% and (6.76 ± 0.38)%, respectively. In both F-1 and F-2, the configuration of glycosidic bonds was α-type, with a certain degree of acetylation and sulfation. Both LMWFs could scavenge 1,1-diphenyl-2-picrylhydrazyl and 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) cationic radicals and showed certain reducing power in the potassium ferricyanide reduction assay. These antioxidant properties were concentration dependent. The contents of polyuronide and galactose in the glycan chain of F-1 was relatively high, so its antioxidant activity was superior to that of F-2 under the same dosage conditions. These findings provide a theoretical basis for the application of LMWFs as excellent natural antioxidants in various fields such as health food and cosmetics.